2012
DOI: 10.1346/ccmn.2012.0600301
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Synthesis Conditions on the Formation of a Kaolinitemethanol Complex and Simulation of its Vibrational Spectra

Abstract: Kaolinite is often used as a base for the synthesis of new organo-mineral nanomaterials designed for applications in industry and in environmental protection. To make the mineral structure more likely to interact with organic molecules, a kaolinite-methanol complex (KM) can be used. In the present study, different experimental procedures were tested to investigate the formation of the KM. The kaolinitedimethyl sulfoxide intercalation compound (KDS), either wet or dried, was used as a pre-intercalate. The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 52 publications
4
28
0
Order By: Relevance
“…However, the band at 3619 cm −1 is shown to be unshifted from the original kaolinite, modified kaolinite, DMSO intercalated kaolinite, and now in the methanol intercalated kaolinite; this is in fact in agreement with 3620 cm −1 wavelength obtained by [45]. The doubly split weak broad band at 3533 cm −1 is ascribed to the externally adsorbed water as suggested by [45,50]; this band has also been considered as the OH stretching of methanol molecules and/or of water molecules formed during the esterification reaction of kaolinite inner-surface OH groups and methanol molecules [51]. The region around 3021 to 2800 cm −1 is marked by the three-split band and is ascribed to the methanol-kaolinite interaction.…”
Section: Ft-irsupporting
confidence: 88%
“…However, the band at 3619 cm −1 is shown to be unshifted from the original kaolinite, modified kaolinite, DMSO intercalated kaolinite, and now in the methanol intercalated kaolinite; this is in fact in agreement with 3620 cm −1 wavelength obtained by [45]. The doubly split weak broad band at 3533 cm −1 is ascribed to the externally adsorbed water as suggested by [45,50]; this band has also been considered as the OH stretching of methanol molecules and/or of water molecules formed during the esterification reaction of kaolinite inner-surface OH groups and methanol molecules [51]. The region around 3021 to 2800 cm −1 is marked by the three-split band and is ascribed to the methanol-kaolinite interaction.…”
Section: Ft-irsupporting
confidence: 88%
“…In the XRD pattern of ZK-UMe(wet), the complete displacement of U with Me and the formation of wet kaolinite-Me complex is clearly demonstrated by the shift of the whole (001) reflection from 1.07 nm to 1.11 nm [41]. The 1.11-nm basal spacing of the wet kaolinite-Me intercalation complex synthesized using the kaolinite-U pre-intercalation complex agrees well with the literature results with kaolinite-DMSO and kaolinite-NMF pre-intercalates [10,12,15,19,29,30,[33][34][35][36]41]. After drying the wet kaolinite-Me complexes at room temperature, the (001) reflections of the expanded phase decreased to 0.86 nm (ZK-U-Me(air-dry) sample), which is close to the value (d 001 = 0.88 nm) reported by Cheng et al [38] for similar air-dried complex prepared from kaolinite-U pre-intercalate.…”
Section: Xrd Analysissupporting
confidence: 89%
“…From the DMSO and NMF pre-intercalates, the formation of a kaolinite-Me complex with basal spacing of 1.11-1.13 nm was established in methanol-wet state [10,12,15,19,29,30,[33][34][35][36]41], but on air-drying, a contraction down to 0.93-0.86 nm was observed [12,15,19,38,41]. Using elemental and thermal analysis results, Tunney and Detellier [7], Komori et al [15], and Matusik and Klapyta [36] calculated the values of x=0.87, x=0.36, and x=0.48, respectively, for the supposed chemical formula of In spite of the more eco-friendly behavior of U, there are only two studies reported in the literature [34,41], where the kaolinite-U pre-intercalate was used to synthesize kaoliniteMe complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, the variety of the guest species that are intercalated into kaolinite layers has also been extended. As an intermediate to further intercalate large guest species, methoxy-modified kaolinite has been paid great attention to [15,[22][23][24][25]. So far, the intercalation of kaolinite by inserting series alkylamines [15,22,26], series quaternary ammonium salts [23,27], series silanes with an amino group, benzyl alkyl ammonium chlorides [28,29], series fatty acids and salts [30,31] into kaolinite layers by taking a methanol-grafted kaolinite compound as a precursor has been successfully performed.…”
Section: Introductionmentioning
confidence: 99%